2000
DOI: 10.1063/1.127067
|View full text |Cite
|
Sign up to set email alerts
|

Gain in 1.3 μm materials: InGaNAs and InGaPAs semiconductor quantum-well lasers

Abstract: The absorption and gain for an InGaNAs/GaAs quantum-well structure is calculated and compared to that of a more conventional InGaAs/InGaPAs structure, both lasing in the 1.3 μm range. Despite significant differences in the band structures, the gain value is comparable for high carrier densities in both structures and the transition energy at the gain maximum shows a similar blueshift with increasing carrier density. For low and intermediate carrier densities, the calculated gain in the InGaPAs system is signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
34
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(38 citation statements)
references
References 18 publications
4
34
0
Order By: Relevance
“…21 The maximum net gain of GeOI is $2500 cm À1 at k ¼ 1593 nm, comparable to III-V semiconductor QWs under a similar injection level of Dn $ 1 Â 10 19 cm À3 . 22 In addition to the optical gain at 1580-1605 nm, the optical bleaching spans from 1530 to 1605 nm, as shown in Fig. 2(b).…”
mentioning
confidence: 96%
“…21 The maximum net gain of GeOI is $2500 cm À1 at k ¼ 1593 nm, comparable to III-V semiconductor QWs under a similar injection level of Dn $ 1 Â 10 19 cm À3 . 22 In addition to the optical gain at 1580-1605 nm, the optical bleaching spans from 1530 to 1605 nm, as shown in Fig. 2(b).…”
mentioning
confidence: 96%
“…[1][2][3][4][5][6][7][8] Compared with InGaAsP lasers at the same emission wavelength, GaInNAs lasers have the smaller temperature sensitivity of threshold current, and hence, higher characteristic temperature T 0 as predicted theoretically. 1,9 However, the recent reports show that the defect-related nonradiative recombination is still severe in this material 10 due to the difficulty in the growth of highquality nitride compounds.…”
Section: H Riechertmentioning
confidence: 87%
“…Figure 1 shows the measured pressure dependence of lasing energy, E lase , in GaInNAs together with the theoretical expectation of the ⌫ minimum, in GaInAs, and the nitrogen level. 2,3 The GaInAs has the same In content as GaInNAs studied. It is shown that as pressure increases the ⌫ minimum increases relatively rapidly while the N level increases a bit slowly.…”
Section: H Riechertmentioning
confidence: 99%
“…Within the band anti-crossing model, although there is no direct coupling between the nitrogen band and the valence bands, there is an indirect interaction through the coupling with the conduction band [10][11][12] . A 10x10 effective mass Hamiltonian is used for energy band structure calculations of an InGaNAs/GaAs QW including the conduction-valence interaction with the spin degenerate nitrogen band.…”
Section: Theoretical Modelmentioning
confidence: 99%